Synthesis and Structural Characterization of Ni(II), Cu(II), Zn(II) and Cd(II) Complexes of Bis(2-amino-1,3,4-thiadiazole) - Adiguzel, R.; Ergin, Z.; Sekerci, M. (Asian Journal of Chemistry, 2010)
In this study, the ligand bis(2-amino-1,3.4-thiadiazole) (L) has been synthesized by the reactions of oxalic acid with thiosemicarbazide The ligand and Ni(II), Cu(II), Zn(II), Cd(II) complexes have been synthesized and its structures of these compounds have been deter-mined by elemental analysis. spectrometric and TGA/DTA, magnetic susceptibility and molar conductivity measurements. Coordination numbers of monomeric Ni(I I) and Cd(II) complexes are six and four, respectively. The coordination numbers of dimeric Cu(II) and Zn(II) complexes are live and four. From the elemental analysis and mass spectral data, the complexes were pi posed to have the formula[Ni(L)(2)(SO4)H2O]0 5DMF 2H(2)O center dot[Cu(L)(SO4)H2O](2)center dot DMF 2H(2)O, [Zn(L)(NO3)](2) 2NO(3)center dot 2DMF center dot H2O and [Cd(L)(2)] 2NO(3)center dot 1.5DMF center dot H2O. Ni (II) and Cu(II) complexes are paramagnetic and non-electrolytes. The molar conductance data revealed that zinc(II) and cadmium(II) complexes are 1 2 electrolytes.
Keywords: Bis(2-amino-1,3,4-thiadiazole); Metal complexes